2018
DOI: 10.1021/acsami.7b15969
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the H2 Evolving Activity of Benzenehexathiolate Coordination Frameworks and the Effect of Film Thickness on H2 Production

Abstract: The design of earth-abundant catalysts for the electrochemical production of H from water is important for the realization of a sustainable energy future. Incorporation of molecular catalysts into extended frameworks has emerged as a viable strategy for improving catalytic performance and durability while maintaining a high degree of control over the structure and properties of the catalytic active site. Here, we investigate benzenehexathiolate (BHT) coordination frameworks as electrocatalysts for the hydrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
85
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(85 citation statements)
references
References 62 publications
0
85
0
Order By: Relevance
“…And so, many MOFs are used indirectly in electrocatalytic applications as precursor materials for the production of porous carbon‐based ORR catalysts through the pyrolysis . Fortunately, some conductive MOFs have recently been developed, which can be directly used in electrocatalytic applications.…”
Section: Introductionmentioning
confidence: 99%
“…And so, many MOFs are used indirectly in electrocatalytic applications as precursor materials for the production of porous carbon‐based ORR catalysts through the pyrolysis . Fortunately, some conductive MOFs have recently been developed, which can be directly used in electrocatalytic applications.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular species incorporated into MOF assemblies forming microstructured films have demonstrated their viability for the catalysis of electrochemical reactions -primarily small molecule activation. A wide variety of MOF architectures (UiO, NU-1000, PCN, MOF-525) functionalized with molecular transition-metal catalysts, have been employed for CO 2 reduction [123,131], hydrogen evolution [111,175], oxygen reduction [27], and water oxidation [140,145]. A recent review highlights the scope of work in this field [34].…”
Section: Kinetic Benchmarking Of Electrocatalytic Mofsmentioning
confidence: 99%
“…Another design consideration towards electrocatalytic MOFs and COFs is optimizing the balance of active sites, which are increased with film thickness, and mass and charge transfer, which follow the opposite trend. To this end, a recent investigation utilizing voltammetry, capacitance and impedance measurements found that Co‐benzene hexatiolate frameworks thicknesses of ∼250 nm offered the best compromise between these factors and resulted in the highest performing systems (Downes et al ). A Cu‐based MOF grown onto graphene also exhibited high HER activity in acidic media (Jahan et al ).…”
Section: Mof and Cof Electrochemical Hydrogen Evolution And Oxygen Evmentioning
confidence: 99%